Multi-modal Analysis of Courtship Behaviour in the Old World Leishmaniasis Vector Phlebotomus argentipes - Bray, Daniel P.; Khatijah, Yaman; Underhilll, Beryl A.; Mitchell, Fraser; Carter, Victoria; Hamilton, James G.C. (PLOS, 2014)
Background